The Effectiveness of Self-Directed Learning Readiness on Competency Achievement of Basic Nursing Clinical Practice Students - Anggia Astuti; Dodi Wijaya; Nur Yuliani; Zainal Abidin; Rizeki Dwi Fibriansari (KHD Production, 2023)
Basic Nursing Clinical Practice is the first clinical learning experience for vocational nursing students. The achievement of complete competence will provide a positive experience, ability, willingness to learn actively and independently, and direct continuous learning so that competent vocational nurse graduates are achieved. Self-Directed Learning Readiness (SDLR) is a condition where students have full control in the process of making decisions related to their learning and accept full responsibility for it, even though later they need help and advice from lecturers and Clinical Instructors. Therefore, this research was conducted to determine the effectiveness of SDLR on the competency achievement of basic nursing clinical practice students. This study used a quasi-experimental design with one group pretest and posttest design. The sampling technique used total sampling, with as many as 91 respondents. Respondents were 2nd semester D3 Nursing Study Program students. The analysis used an independent sample t-test, with a 95% degree of confidence. The results of statistical tests using the Independent T-Test showed that there was a positive effect of SDLR on the Competency Achievements of Basic Nursing Clinical Students with a p-value <0.05. Of course, a high level of Self Directed Learning Readiness, can have a positive impact on student competency outcomes in carrying out Nursing Clinical Practice, where competency achievement targets will be met. Achievement of plenary competence will provide a positive experience, ability, willingness to learn actively and independently, and direct continuous learning so that competent vocational nurse graduates are achieved.